Automated Evaluation of Telugu Text Essays Using Latent Semantic Analysis - et. al., M Varaprasad Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The most productive strategy to improve students' ability to write is to have direct and as much as possible teacher input. However, the workload of the teacher is greatly increased. Automated systems are increasingly required to help students write essays. In the field of educational assessment technology, automated test evaluation is becoming more and more common. We present a framework that is modelled on the programme, following which the school-teachers in the BPDAV School and Govt. High School Hyderabad, Telangana, India present the automatic evaluator of student essays in the Telugu language. Language skills; the structure of the essay and the contents that fit the subject are the principal requirements for evaluating the essays. In this context, we have established a scheme focused on latent semantical analysis and the theory of rhetorical structure. The method has been evaluated in more than 600 different essays, written in different manuscripts by schoolchildren. Overall0.82 with the teacher's assessment was achieved in our method.